Standard approach and future perspective for the management of benign prostatic hyperplasia from a health-economics point of view: the role of transperineal laser ablation - Lorenzoni, Valentina; Palla, Ilaria; Manenti, Guglielmo; Ditonno, Pasquale; de Reijke, Theo M.; Turchetti, Giuseppe (Frontiers in Urology, 2023)
Introduction Benign prostatic hyperplasia (BPH) is a common diagnosis among the ageing male population over 60 years and it is associated with the development of lower urinary tract symptoms (LUTS): dysuria, nocturia, increased frequency of urination, etc. LUTS negatively affect the patient’s daily activities and the quality of life. Patients with severe and persisting symptoms, not responding to pharmacological therapy, are candidates for surgical intervention. Transurethral resection of the prostate (TURP) has been the gold standard for surgical approach despite it can be associated with significant complications. Indeed, laser vaporization or enucleation are today the most broadly used surgical techniques and other minimally invasive surgical therapies (MISTs) have been introduced to reduce some complications during- and post-surgery. Moreover, a new micro-invasive approach for LUTS is represented by EchoLaser SoracteLite™ transperineal laser ablation (TPLA), an innovative, safe and feasible approach that can be performed under local anaesthesia and in an outpatient setting. Objective The paper aims to analyse and discuss the economic implications of standard surgical techniques and innovative approaches with a focus on TPLA thought a literature review. Results The literature review highlights that at present there are few studies related to the economic implications of surgical therapies for LUTS. Preliminary results show that the TPLA is a promising technique in terms of clinical and economic benefit for the treatment of obstructive LUTS. Furthermore, TPLA can be performed in an outpatient setting implying an advantage from an economic and also organizational point of view, in particular in a health emergency situation. Conclusions Economic literature on minimally invasive techniques and surgical approaches for the treatment of BPH is still lacking. Multicentre and long-term economic studies are needed to assess the estimated disease burden. However, direct and indirect costs associated with TPLA are minimized vs TURP and laser vaporization/enucleation.